Dinah between Rape and Seduction: Maarten van Heemskerck and Renaissance Attitudes towards Gender and Conflict - Bokody, Péter (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
In 1569, Gerard de Jode published in Antwerp Maarten van Heemskerck’s Old Testament print series about Dinah, daughter of Jacob. In these images, Heemskerck reinterprets the Old Testament narrative from a deeply misogynistic standpoint, disputing the Biblical claim that Shechem raped Dinah. This article traces the sporadic representations of the episode in prints and paintings and examines visual strategies that emphasize male vulnerability over the suffering of the female victim. Heemskerck’s artistic choices are then evaluated in the context of certain exegetical differences between Martin Luther and John Calvin.